2005
DOI: 10.1152/ajprenal.00384.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nonosmotic release of vasopressin and renal aquaporins in impaired urinary dilution in hypothyroidism

Abstract: -The purpose of this study was to examine protein expression of renal aquaporins (AQP) and ion transporters in hypothyroid (HT) rats in response to an oral water load compared with controls (CTL) and HT rats replaced with L-thyroxine (HTϩT). Hypothyroidism was induced by aminotriazole administration for 10 wk. Body weight, water intake, urine output, solute and urea excretion, and serum and urine osmolality were comparable among the three groups at the conclusion of the 10-wk treatment period. One hour after o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 24 publications
0
30
0
8
Order By: Relevance
“…Additionally, the impaired cardiac function that often occurs with advanced myxedema can lead to an elevation in plasma AVP levels, and in experimental hypothyroidism, the impaired response to an acute water load was reversed by a V 2 R antagonist. 32 Whether hyponatremia develops at any stage of disease progression depends on the relative balance between water intake and excretory capacity; since maximal solute-free water clearance decreases as these defects become more pronounced, the incidence of hyponatremia increases as the severity of the underlying hypothyroidism worsens.…”
Section: Nephrogenic Syndrome Of Inappropriate Antidiuresismentioning
confidence: 99%
“…Additionally, the impaired cardiac function that often occurs with advanced myxedema can lead to an elevation in plasma AVP levels, and in experimental hypothyroidism, the impaired response to an acute water load was reversed by a V 2 R antagonist. 32 Whether hyponatremia develops at any stage of disease progression depends on the relative balance between water intake and excretory capacity; since maximal solute-free water clearance decreases as these defects become more pronounced, the incidence of hyponatremia increases as the severity of the underlying hypothyroidism worsens.…”
Section: Nephrogenic Syndrome Of Inappropriate Antidiuresismentioning
confidence: 99%
“…In this rat model of hypothyroidism the increase in plasma AVP was associated with upregulation of AQP2. Moreover, a V2 receptor antagonist has been shown in this rat model of hypothyroidism to reverse the increased AQP2 and the impaired response to an acute water load (Figure 4) (44). The hypothyroid rats also demonstrated a diminution in maximal urinary concentration which was associated with a defect in the counter-current concentrating mechanism (45).…”
Section: Hypo-and Hyperthyroidismmentioning
confidence: 77%
“…Advanced hypothyroidism may be associated with a decrease in blood pressure secondary to diminished myocardial contractability and heart rate. These hemodynamics are mimicked in hypothyroid rats and are reversed with thyroxin replacement (44). These impaired systemic hemodynamics would be expected to activate baroreceptor-mediated, non-osmotic AVP release and indeed this is the case.…”
Section: Hypo-and Hyperthyroidismmentioning
confidence: 96%
See 1 more Smart Citation
“…The increase in ADH levels has been mainly attributed to the hypothyroidism-induced decrease in cardiac output, which stimulates the carotid sinus baroreceptors and induces the release of ADH (11,12,13,14). Thus, hyponatremia in most of hypothyroid patients is the result of the inability to suppress maximally the secretion of ADH, which results in reduced water excretion (3,15). Indeed, it has been shown that the impaired water excretion in hypothyroidism is mediated through the upregulation of ADH-induced acquaporin-2 expression in the collecting tubules (15).…”
Section: Possible Mechanisms Of Hyponatremia In Patients With Hypothymentioning
confidence: 99%